Common Genetic Variants and Response to Atrial Fibrillation Ablation. (April 2015) - Shoemaker, M. Benjamin; Bollmann, Andreas; Lubitz, Steven A.; Ueberham, Laura; Saini, Harsimran; Montgomery, Jay; Edwards, Todd; Yoneda, Zachary; Sinner, Moritz F.; Arya, Arash; Sommer, Philipp; Delaney, Jessica; et al.
<x xml:space="preserve">Abstract</x> Background— Common single nucleotide polymorphisms (SNPs) at chromosomes 4q25 (rs2200733, rs10033464 near PITX2), 1q21 (rs13376333 in KCNN3), and 16q22 (rs7193343 in ZFHX3) have consistently been associated with the risk of atrial fibrillation (AF). Single-center studies have shown that 4q25 risk alleles predict recurrence of AF after catheter ablation of AF. Here, we performed a meta-analysis to test the hypothesis that these 4 AF susceptibility SNPs modulate response to AF ablation. Methods and Results— Patients underwent de novo AF ablation between 2008 and 2012 at Vanderbilt University, the Heart Center Leipzig, and Massachusetts General Hospital. The primary outcome was 12-month recurrence, defined as an episode of AF, atrial flutter, or atrial tachycardia lasting >30 seconds after a 3-month blanking period. Multivariable analysis of the individual cohorts using a Cox proportional hazards model was performed. Summary statistics from the 3 centers were analyzed using fixed effects meta-analysis. A total of 991 patients were included (Vanderbilt University, 245; Heart Center Leipzig, 659; and Massachusetts General Hospital, 87). The overall single procedure 12-month recurrence rate was 42%. The overall risk allele frequency for these SNPs ranged from 12% to 35%. Using a dominant genetic model, the 4q25 SNP, rs2200733, predicted a 1.4-fold increased risk of recurrence (adjusted hazard ratio, 1.3 [95% confidence intervals, 1.1–1.6]; P=0.011). The remaining SNPs, rs10033464 (4q25), rs13376333 (1q21), and rs7193343 (16q22) were not significantly associated with recurrence. Conclusions— Among the 3 genetic loci most strongly associated with AF, the chromosome 4q25 SNP rs2200733 is significantly associated with recurrence of atrial arrhythmias after catheter ablation for AF.